IMPROVING STUDENTS’ DICTATION ABILITY USING ANIMATED SHORT MOVIE THE FANCY GENTLEMEN AS A MEDIA OF LEARNING - Ronaldo Jonathan Kindangen; Jim Ronny Tuna; Fivy A. Andries (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this research to find out the effectiveness of using the movie as a media of learning to improve students listening skills especially in Dictation. The researcher uses Pre – Experimental Research and the sample of the study is the 9th grade students in SMP Anugrah Tondano and the total number of the sample are 20 students. The instrument of this study is an answer sheet consist of 20 numbers that students have to fill with word. The data were calculated by the result of students’ Pretest are 41 and Posttest are 77. The students gained scores from Pretest to Posttest are 36. The result of this research showed that using a movie as a media of learning to improve students listening skills especially in dictation is effective.